Exclusive Updates! Brought to you by your local QUD - Coppock, Elizabeth; Beaver, David (Proceedings of the Amsterdam Colloquium, 2011)
We propose a dynamic semantics within a variant of standard type theory (Ty3; Beaver 2001) in which contexts include not only a common set of beliefs, but also a question under discussion (QUD) whose answers are information states consisting of world-assignment pairs, along with a strength ranking over such answers. The proposed framework satisfies several desiderata arising from the behavior of exclusives (e.g. only, just, mere and sole), including: (i) the possibility of presupposing a question; (ii) quantificational binding into such presupposed questions; (iii) the expressibility of presuppositional constraints regarding the strength ranking over the answers to the question under discussion; (iv) compositional derivation of logical forms for sentences.